2003
DOI: 10.2139/ssrn.472903
|View full text |Cite
|
Sign up to set email alerts
|

The Case of the Missing Productivity Growth: Or, does Information Technology Explain why Productivity Accelerated in the United States but not the United Kingdom?

Abstract: Solow's paradox has disappeared in the United States but remains alive and well in the United Kingdom. In particular, the U.K. experienced an information and communications technology (ICT) investment boom in the 1990s in parallel with the U.S., but measured total factor productivity has decelerated rather than accelerated in recent years. We ask whether ICT can explain the divergent TFP performance in the two countries. Stories of ICT as a 'general purpose technology' suggest that measured TFP should rise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 47 publications
7
83
1
1
Order By: Relevance
“…These studies all attributed a high proportion of the productivity resurgence to ICT, and found that most of the improvement was due to the use of ICT equipment by other industries (capital deepening) rather than to the production of ICT equipment by the ICT industries themselves. Similar studies have been published for the U.K. (Oulton (2002); Oulton and Srinivasan (2005); Marrano et al (2009)), and for the G7 (Schreyer (2000)); a U.S.-U.K. comparison is Basu et al (2004) and an EU-U.S. comparison is van Ark, O'Mahony and Timmer (2008). These all 2 Perron (1989) found that the Great Depression had a permanent effect on the level of U.S.…”
Section: The Importance Of Ictsupporting
confidence: 70%
“…These studies all attributed a high proportion of the productivity resurgence to ICT, and found that most of the improvement was due to the use of ICT equipment by other industries (capital deepening) rather than to the production of ICT equipment by the ICT industries themselves. Similar studies have been published for the U.K. (Oulton (2002); Oulton and Srinivasan (2005); Marrano et al (2009)), and for the G7 (Schreyer (2000)); a U.S.-U.K. comparison is Basu et al (2004) and an EU-U.S. comparison is van Ark, O'Mahony and Timmer (2008). These all 2 Perron (1989) found that the Great Depression had a permanent effect on the level of U.S.…”
Section: The Importance Of Ictsupporting
confidence: 70%
“…Faster TFP growth in producing ICT products can, conceptually, raise aggregate TFP and labor productivity growth through several channels (see, for example, Basu, et al, 2003). Most directly, it raises aggregate TFP growth by raising it in the industries that produce ICT products.…”
Section: Us Experience: An Easing In the Ict Revolution?mentioning
confidence: 99%
“…However, non-ICT-producing U.S. industries also showed faster TFP growth in the late 1990s or early 2000s (e.g., Basu et al, 2003, andBosworth andTriplett, 2006). An important channel through which declining ICT prices can affect measured TFP is by fostering complementary innovations, such as business reorganization, to take advantage of an improved ability to manage information and communications.…”
Section: Us Experience: An Easing In the Ict Revolution?mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of substantial productivity growth in the service sector, and in the retail sector in particular. According to Basu et al (2003), the productivity growth in wholesale and retail trade between 1995 and 2000 was the second highest among all sectors in the US, second only to information technology producing sectors. Third, policies that affect the size of establishments are likely to be costly as large establishments account for a disproportionate fraction of output and employment.…”
Section: Introductionmentioning
confidence: 99%